If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 103 + -1(6x + 8) = 6(x + 5) + x Reorder the terms: 103 + -1(8 + 6x) = 6(x + 5) + x 103 + (8 * -1 + 6x * -1) = 6(x + 5) + x 103 + (-8 + -6x) = 6(x + 5) + x Combine like terms: 103 + -8 = 95 95 + -6x = 6(x + 5) + x Reorder the terms: 95 + -6x = 6(5 + x) + x 95 + -6x = (5 * 6 + x * 6) + x 95 + -6x = (30 + 6x) + x Combine like terms: 6x + x = 7x 95 + -6x = 30 + 7x Solving 95 + -6x = 30 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 95 + -6x + -7x = 30 + 7x + -7x Combine like terms: -6x + -7x = -13x 95 + -13x = 30 + 7x + -7x Combine like terms: 7x + -7x = 0 95 + -13x = 30 + 0 95 + -13x = 30 Add '-95' to each side of the equation. 95 + -95 + -13x = 30 + -95 Combine like terms: 95 + -95 = 0 0 + -13x = 30 + -95 -13x = 30 + -95 Combine like terms: 30 + -95 = -65 -13x = -65 Divide each side by '-13'. x = 5 Simplifying x = 5
| 2-5+2-6-9= | | (0.8-x)(0.7-x)-(0.3)(0.2)=0 | | 102-(6x+8)=6(x+5)+x | | 2(2-8x)+5x=6(3+5x) | | Y+8=37 | | x-4=x | | 5(x-3)-7x=-23 | | 7(2-x)+3=5(3-x) | | x-7.7=-3.6 | | (x+12)/x=3 | | 6(n-8.2)=-18.6 | | 69=4x-11 | | Y^2+10y+16/y^2+16y+64 | | 36=3v-12 | | x/14=-20 | | 7x+4x=15 | | 8(2-x)+3(x-1)=3x-1 | | (2-x)+3(x-1)=3x-3 | | 4=-8v+4(v+8) | | 2x-x=-9-3 | | 3w^2-370w+9000=0 | | 4x+3-6x=12-19x+17x-9 | | 2x+4=x-17 | | x+4(9-x)=x-12 | | 3X+2+5X-1=5-3X+5 | | 3w^2-185w+9000=0 | | 5x+14-4=0 | | 8x-4=-2+6x | | 3X+2+5X-1=5-13X+5 | | x^2-120x+10=0 | | 2z-28=-32+6z | | log(y-35)=5t |